Generalised optimised design of single‐resonant AC current regulators. Issue 10 (1st May 2019) - Elkayam, M.; Kuperman, A.
Abstract : This Letter generalises frequency‐domain oriented design guidelines for optimised single‐resonant three‐parameter AC current regulators for grid‐connected converters. Unlike in previously established set of design guidelines, possible practical restrictions imposed by relatively low‐switching frequency are taken into account in the proposed methodology. In addition, resonant term bandwidth is selected according to the desired robustness to fundamental frequency variations. As a result, a closed set of three non‐linear equations is created. The solution maximises the loop gain crossover frequency for a given phase margin while respecting frequency robustness and resonant gain restrictions, set a priori.